An analysis of intrinsic motivators about the effect of social media usage on artistic creativity in university in China - Wang, Lei; Ismail Kamal, Julina Binti (Creativity Studies, 2024)
With the development of the information age, social media has become an important channel for students to communicate, interact and obtain information online. This research combines analyses of social media use and factors linked to intrinsic motivation to examine the influence of these factors on university students’ creativity through the Internet. The discussion presented here starts from the viewpoint that intrinsic motivation plays an important role in the correlation between social media and students’ creativity. This study randomly surveyed 416 students from Chinese universities majoring in art to investigate the impact of social media on their levels of creativity. The analysis focused on understanding these students’ intrinsic motivation to engage in Internet use. The conclusions show that social media has a considerable impact on their creativity. Under the influence of intrinsic motivation, students’ creativity can be considerably boosted. Furthermore, it also shows that different intrinsic motivations have different effects on creativity levels. Therefore, the study is suggested that the education sector in China still needs to pay more attention to the development of students’ creative approaches to achieve better educational outcomes.